Suppression of Bridge Flutter Using Suction Control - Shibo Tao (Advances in Civil Engineering)
To verify the effectiveness of the suction-based method for improving flutter stability of long-span bridges, the forced vibration experiments for extracting the flutter derivatives of a section model with and without suction were performed, and the corresponding critical flutter wind speeds of this structure were calculated out. It is shown by the experiment that the flutter stability of the bridge depends on suction configuration. As the suction holes locate at the leeward side of the model, the critical flutter wind speed can attain maximum under the same suction velocity. In the analytical results, it is remarkably effective that the suction control improves the long-span bridge flutter stability.